Analysis of automotive car chair. (2021) - Sekhar Reddy, Pakanati C.; Shariff, Jabihulla; Sreenivasan, M.; Sivakumar, E.R.
Abstract: This work aims to design a car seat and simulate its performance using different standard tests using finite element method (FEM). There are two main components: (1) design; and (2) FEM analyses. We build a generic automotive rear seat with the aid of the software CAD Catia V5. In this analysis, finite element simulations were performed. The software was the well-known finite element solver Hyper mesh and LS-Dyna. In order to verify the correct application of demands from the standard rules, stresses and moving data are obtained from the computer simulation of the seating system in order to make adjustments in the design, if necessary within the permitted limits. This tool allows the refinement of the geometry, materials and so on before production of the prototype to be achieved, thus reducing costs and developing time for the manufacturer.